THE IMPLEMENTATION OF SUPERVISION MANAGEMENT IN AN EFFORTS TO IMPROVE PAI TEACHERS' PERFORMANCE AT SMPN 1 LOHBENER - supriyatin, denny (ASWAJA: Jurnal Pendidikan dan Keislaman, 2025)
This study aims to analyze the implementation of supervisory management and its impact on the performance of Islamic Religious Education (PAI) teachers at SMP Negeri 1 Lohbener, Indramayu Regency. The study used qualitative methods with descriptive data. Subjects included the principal, vice principal, and Islamic Religious Education (PAI) teachers. Data were collected through observation, interviews, and documentation, then analyzed through data reduction, presentation, and verification. The results indicate that supervision is carried out in a structured and continuous manner every semester, encompassing academic supervision for teachers and supervision of educational staff. The supervision process consists of three stages: planning (determining objectives, resource requirements, and the roles of relevant parties), implementation (classroom visits, teaching observations, and personal conversations), and evaluation and follow-up through a summary of supervision results and direct and indirect training. This supervision has a positive impact on improving Islamic Religious Education (PAI) teacher performance, including identifying teacher weaknesses, improving teaching skills, understanding student needs, and improving learning outcomes. Supervision also facilitates policy adjustments to improve educational quality. Supporting factors for successful supervision include school management collaboration, thorough planning, an appropriate approach, and a positive school culture. Barriers include limited time, the number of supervisors, limited understanding of supervision, limited infrastructure, and teachers' mastery of information technology.